THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT IMPLEMENTATION BY ENGLISH TEACHERS OF SENIOR HIGH SCHOOLS IN SIAK - Tengku Meilita Yuharani; Afrianto Afrianto; Fadly Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study is aimed at investigating how autentic assessment has been implemented by English Teachers of Senior High Schools in Siak Regency. Specifically, the objective of this research are: 1) To investigate to what extent the teachers have implemented authentic assessment in teaching English at Senior High Schools in Siak, 2) To obtain data on how the perceptions of English teachers at High schools in Siak on the authentic assessment, 3) To identify obstacles and problems faced by English teachers in implementing Authentic Assessment as part of the 2013 Curriculum at High Schools in Siak. This is a mixed-method research. The sample of this mixed method research were all English teachers of Senior High Schools in Siak Regency selected by total sampling technique (n:39). In order to collect the data, a semi-closed questionnaire was used. The questionnaire was distributed online by using google form platform. The data then analyzed quantitatively and qualitatively. The study shows the authentic assessment implementation is in a good level and receive a good perspective from most of the teachers. Nonetheless, teachers still experienced several problems during the implementation: the lack of time and complexity of the authentic assessment.Keywords: Authentic Assessment, Implementation, Senior High Schools.